1 - La question locale dans le débat constitutionnel au Cameroun : chassé-croisé entre unité et pluralisme: by Hélène-Laure Menthong - Hélène-Laure Menthong (Africa Development, 1997)
The ongoing argument for political liberalisation in Cameroon since 1990 has been an occasion for the de-legitimation/re-legitiination of the political order and a space for the production of new governance norms. It is a site of reformulation of the constitutional order which becomes a reality through the debate about the constitution formally initiated in 1993. Its legitimate local problématique appears as one of the major issues in the symbolic rivalry among political entrepreneurs for hegemony over the state territory. The constitutional debate on the local question then focuses on the crisis of political integration in Cameroon while consecrating the construction of identities and the emergence in the pubic space and in the political arena of such notions as minority, autonomy, federalism and secession. Yet, the cracks in the Cameroonian political system have led to the reconfiguration of the unitary state characterised by the striking of a new 'balance of tensions' between the centre and the periphery, through the constitutionalisation of the commune and the region as a panacea for territorial recomposition.